2015
DOI: 10.4103/1319-3767.161645
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sustained virologic response after discontinuation of nucleos(t)ide analog treatment for chronic hepatitis B

Abstract: Background/Aims:The aim of this study was to identify the predictors for relapse after discontinuation of oral nucleos(t)ide analog treatment for chronic hepatitis B (CHB).Patients and Methods:We evaluated patients who were receiving long-term, regular antiviral therapy with nucleos(t)ide analogs, and subsequently achieved the discontinuation criteria from the Asia-Pacific guideline. After they voluntarily discontinued the drug therapy, data were prospectively collected to observe the potential virologic relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…The cessation criteria were described in all studies. Ten studies discontinued NAs according to the APASL stopping criterion . One study discontinued NAs according to the recommendation from the National Health Plan of Taiwan, China; the clinical physician’s opinion; and sufficient discussion between physicians and patients .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cessation criteria were described in all studies. Ten studies discontinued NAs according to the APASL stopping criterion . One study discontinued NAs according to the recommendation from the National Health Plan of Taiwan, China; the clinical physician’s opinion; and sufficient discussion between physicians and patients .…”
Section: Resultsmentioning
confidence: 99%
“…The low detection limit of HBV DNA ranged from <12 to <1,000 IU/mL. Ten studies reported values of HBsAg at EOT that ranged from 39.8 to 794.3 IU/mL . The duration of the off‐treatment follow‐up ranged from 12 to 157 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several problems associated with long-term NUC treatment, including development of drug resistance, poor adherence, economic burdens, and psychological stressors 9,10. The Asian Pacific Association for the Study of the Liver (APASL) Guidelines recommend that NUC treatment for CHB could be considered successful after serum HBV DNA is undetectable, HBeAg seroconversion has occurred, and alanine aminotransferase levels have normalized for at least 12 months.…”
Section: Introductionmentioning
confidence: 99%